2023
DOI: 10.1002/pbc.30541
|View full text |Cite
|
Sign up to set email alerts
|

Mixed‐methods analysis of decisional regret in parents following a child's death from cancer

Abstract: Background and objectivesDecisional regret is common in bereaved parents. We aimed to identify factors associated with and to explain patterns of parental decisional regret.MethodsWe used a convergent mixed‐methods design including quantitative items and free‐text responses from a survey of parents 6–24 months from their child's death from cancer. Parents expressed whether they had regrets about decisions during the end of their child's life (Yes/No/I don't know) and elaborated with free text. Results of quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…Confirmation bias may partly explain this degree of decision satisfaction, as described in another general pediatric oncology study. 31 Prevalence of hopeful patterns of thought, trust in the medical team, and perceived self-efficacy were previously described as protective against regret, [31][32][33][34] which may also be the case in our sample. Moreover, these constructs are important mitigators of uncertainty-related distress, a source of emotional distress common not only to our pediatric cohort, but another study among adult patients treated with CAR T-cell therapy.…”
Section: Discussionsupporting
confidence: 66%
“…Confirmation bias may partly explain this degree of decision satisfaction, as described in another general pediatric oncology study. 31 Prevalence of hopeful patterns of thought, trust in the medical team, and perceived self-efficacy were previously described as protective against regret, [31][32][33][34] which may also be the case in our sample. Moreover, these constructs are important mitigators of uncertainty-related distress, a source of emotional distress common not only to our pediatric cohort, but another study among adult patients treated with CAR T-cell therapy.…”
Section: Discussionsupporting
confidence: 66%
“…Recent research from the USA has shown that mothers of children who died due to cancer often have decisional regret, especially if their child had significant physical suffering at the end-of-life 9 . The above authors suggested that preparing the parents beforehand about potential symptoms reduced future guilt and regret.…”
Section: Dying Children and Grief In Parentsmentioning
confidence: 99%
“…Parents rated the extent that they agreed with the statement that their child experienced a good death and wrote in additional context. 2,3 The parents' deeply candid free-text responses showed how some parents bristled at these questions and revealed that our (and many others') assumption that it was possible for a child's death to be good created discomfort at best and deep harm at worst: "How the fuck is your child dying considered a 'good death'? Come on.…”
mentioning
confidence: 99%